The role of innovation-led profits in the development of an international financial centre - Bryane Michael (Journal of Innovation and Entrepreneurship, 2024)
Qianhai-an innovation park in Shenzhen-has the possibility of boosting innovation in Hong Kong, Shenzhen and in the wider region. This paper reviews the existing evidence about which policies have promoted profitable innovation in the Qianhai region (Hong Kong and Shenzhen) in the past. We also point to the importance of profitable innovation-rather than just innovation for its own sake. Profits attract and keep firms in an international financial centre. Yet, until we know exactly how much profitability these innovative firms require and how to promote such profitability, the advice given in the literature to Qianhai's and other policymakers will remain woefully inadequate.
Keywords: P48; R12; R58; 650; Cross-border economic zones; Innovation; Qianhai; Special economic zones